Prirastoslovni vidiki načrtovanja donosov - Kadunc, Aleš (Gozdarski vestnik, 2008)
The article deals with the impact of forest growth and yield indicators on yield planning. On the basis of growth and yield research in beech stands, we tried to present the role in forest yield planning of concepts such as site productivity in terms of value (SPvalue), value increment, volume increment, exploitation of SPvalue, rotation period and regeneration period. The significance of current and mean annual value increment course for decision-making about starting stand regeneration is presented. Economic losses as a result of deferred or premature regeneration are shown in the caseof beech stands. The influence of interest rates on yields and culminationtimes of beech stands is also presented.
Keywords: bukovi gozdovi; prirastek; donos; Fagus sylvatica L.